Purification of Calcite, a Key Mineral in Traditional Oriental Medicine, Based on Malayan Berkh Descriptions: The Purification Process of Calcites - Batdorj, Bilegsaikhan; Surenjid, Seesregdorj; Baatar, Seded; Ganbold Samdandorj; Dashjamts, Shagdarsuren; Battogtokh, Gerelmaa; Bai, Buyant; Radnaabzar, Molor (Trends in Immunotherapy, 2025)
The burden of chronic stomach diseases necessitates the widespread utilization of calcite-containing substances proven to safeguard the stomach. Calcite is most common mineral on Oriental medicine with long history and variable purification processing methods. This study delves into the calcite processing methods based on the ancient sutra, comparing diverse sources. Through content analysis, we summarize the key insights from the “Difficulties’ Commentary Malaya” and conduct a comparative sampling to contextualize calcite processing, classification, and potency within other descriptive works. We identify eight distinct methods of processing and utilizing calcite in medicine, with current Mongolian pharmaceutical industries predominantly employing four types: hot, cold, rich, and smooth methods. The criteria for assessing calcite preparation characteristics undergo rigorous testing in Chinese and Mongolian pharmaceutical factories, adhering to specific regulations. Meanwhile, Mongolian pharmaceutical factories in Mongolia enrich traditional criteria by integrating sensitive device analysis with modern physical technology.